1971
DOI: 10.1172/jci106507
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-dependent peroxidative metabolism in the alveolar macrophage

Abstract: A B S T R A C T Phagocytosis by rabbit alveolar macrophages (AM) is accompanied by increases in 02 consumption, glucose oxidation, and H202 formation. Two aspects of the interrelations between these metabolic features of phagocytosis have been studied.First, the following evidence indicates that glutathione, glutathione reductase, and peroxidase serve as a cytoplasmic shuttle between H202 and NADPH-dependent glucose oxidation: (a) AM contain 5.9 mi'moles of reduced glutathione per 108 cells and exhibit glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1971
1971
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…2C are, first, that there is no correlation with respect to the run number, which proves that the influence of the other substances in macrophages on the determination of GSH has been minimized; and second, that the distribution of values does not follow Gaussian statistics. The mean GSH content for 20 cells is 5.8 Ϯ 2.9 fmol (mean Ϯ SD), which is consistent with the literature value (4.8 -6.0 fmol) (26). A histogram of the data (shown in Fig.…”
Section: Analysis Of Individual Cellssupporting
confidence: 90%
See 1 more Smart Citation
“…2C are, first, that there is no correlation with respect to the run number, which proves that the influence of the other substances in macrophages on the determination of GSH has been minimized; and second, that the distribution of values does not follow Gaussian statistics. The mean GSH content for 20 cells is 5.8 Ϯ 2.9 fmol (mean Ϯ SD), which is consistent with the literature value (4.8 -6.0 fmol) (26). A histogram of the data (shown in Fig.…”
Section: Analysis Of Individual Cellssupporting
confidence: 90%
“…A total of 20 cells were analyzed consecutively. If the content of GSH in each cell is calculated by comparison of peak height against the peak height of GSH standard, the average amount of GSH in single macrophage is (2.8 Ϯ 1.7) fmol (mean Ϯ SD), which is about one-half of the literature value (4.8 -6.0 fmol) (26). This means that the substances in the cells probably interfere with the determination of GSH.…”
Section: Quantification Of Gsh In Individual Macrophagementioning
confidence: 92%
“…Several investigators have studied the role of en dogenous scavengers of oxygen intermediates in mac rophages [30][31][32][33][34], Murray et al [33] demonstrated that in vitro lymphokine-activated peritoneal macro phages from normal mice increased activities of SOD, GSH Px and catalase in association with augmented production of O; and H^CT. In our experiments, in vitro treatment with LPS similarly increased catalase activity in both MRL/1 (by 39%) and MRL/n (by 34%) macrophages, which confirmed an earlier find ing of Murray et al [33].…”
Section: Discussionmentioning
confidence: 99%
“…^+ PhSBu-/ + /-BuS- (83) fast and hydrogen abstraction often predominates [166,168,169]. Radical attack on the sulfur of the comparable disulfides, a "softer" and more polarizable center, is faster [166,168,169]; for example, see eqs 81-83. Nucleophilic substitution reactions on the Ο-Ο bond of benzoyl peroxide are much faster than on dialkyl peroxides, as expected, since the leaving group is better.…”
Section: I One-electron Versus Two-electron Transfersmentioning
confidence: 99%